Comportamento reológico dos solos em umidades próximas aos limites de Atterberg, utilizando o Squeeze-flow - Notaro, Cauêh Castro (2012)
The study of the rheological behavior relating the interaction between the soil particles with the fluid is of great importance for the performance and application engineering works The rheology is most used in Civil Engineering to evaluate the interaction between the solid particles and water paste, mortar and concrete. Clay is a material inconsistency, caused by the incipient weathering of granitic rocks, containing large amounts of small fragments of feldspar and quartz, and other accessory minerals of the rock and is used in mortar. This research aims to characterize and evaluate the rheological behavior of five soils with different consistencies and nine grit of the Metropolitan Region of Recife (RMR) used in mortars, through conventional methods of assessing the consistency of the soil, such as limits on liquidity and plasticity and compare with the behavior obtained in the test with the Squeeze-Flow. The test for the study is the compression rheology of the sample by means of two parallel plates, measuring both the applied load and resultant displacement. We obtained the values of consistency limits of complying with recommendations of the Brazilian Association of Technical Standards. The samples were molded in a cylindrical shape with a diameter of 101 mm and height 10 mm, the same water content used to obtain the liquid limit of the apparatus Casagrande and moisture corresponding to the liquid limit and plasticity and subsequently compressed by measures load and displacement. The results show that the more clayey materials present higher liquidity limits and plasticity indexes. The data obtained in tests with the Squeeze Flow show the influence of the amount of water to mix with the ground and the load versus displacement curve which has elastic behavior, plastic and plastic hardness depending on the amount of water, and the consistency of fine material . The interaction between particles and water using the Squeeze-Flow showed that the technique is able to assess and evaluate, with sensitivity to the shape of load versus displacement curve of the studied materials used for the analysis of behavior.